Stakeholder engagement analysis and performance over time - Stocker, Fabricio (2020)
The literature on stakeholder engagement states that cooperative relationships can be achieved through engagement strategies that range from communication to partnership and involvement, thus leading to a greater level of commitment and engagement between the organization and its stakeholders. Despite this, there is no clear evidence in the literature to support this idea that higher levels of stakeholder engagement have a positive effect on the company\'s performance. This thesis aims to address that gap by analyzing the different engagement strategies and understanding how different nuances of stakeholder-organization relationships affect the quality of the engagement and its impact on firm performance over time. This study was carried out in organizations in the energy sector that disclose their sustainability reports through the international GRI platform. This study has two distinct methodological designs: i) qualitative stage: data collection from sustainability reports and application of the content analysis method to the engagement actions over the 6 years. ii) quantitative stage: to assess the impact of engagement actions on the social (CSP), environmental (CEP), and financial (CFP) performance of companies over time. The multivariate analysis is mainly carried out through panel data regression and mediation analysis. The results of this research are revealing and contrast with some of the theoretical arguments about financial, social and environmental gains and returns, while emphasizing that although performance over time is positive, when the different levels are evaluated and their effect on the short and in the long term, the most intense relationships with a high level of engagement do not have a positive relationship with social performance in the long term, but in the short term. The research project intends to elucidate key issues of strategy studies, related to practices that generate better results and performance for companies. It also aims to provide a managerial contribution by clarifying what strategies and actions have had a greater impact over time on company performance and can improve the management of companies and serve the interests of their stakeholders.